Protective Effects of Resveratrol and Apigenin Dietary Supplementation on Serum Antioxidative Parameters and mRNAs Expression in the Small Intestines of Diquat-Challenged Pullets - Zhou, Ning; Tian, Yong; Liu, Wenchao; Tu, Bingjiang; Xu, Wenwu; Gu, Tiantian; Zou, Kang; Lu, Lizhi (Frontiers in Veterinary Science, 2022)
Poultry as a large-scale intensive farming is vulnerable to oxidative stress. Resveratrol and apigenin are recognized to have many beneficial bioactive functions. This study tested the hypothesis that dietary resveratrol and apigenin supplementation alleviates oxidative stress in the small intestine of diquat-challenged pullets. A total of 200 healthy pullets were randomly divided into four treatment groups: control group fed with a basal diet (CON), diquat group fed with a basal diet (DIQ), resveratrol group fed with a basal diet containing 500 mg/kg resveratrol (RES), and an apigenin group fed with a basal diet containing 500 mg/kg apigenin (API) and injected intraperitoneally with either 1 ml of saline (CON) or 8 mg/kg body weight of diquat (DIQ, RES, and API) to induce oxidative stress. The day of the injection was considered as day 0. The results indicated that resveratrol and apigenin were able to decrease the malondialdehyde (MDA) level and upregulate total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX) levels in serum on day 1 and 10 after being diquat-challenged. In addition, resveratrol increased mRNA expression of NQO1 (NAD(P)H dehydrogenase quinone 1) and HO-1 (heme oxygenase-1) in ileum and jejunum on day 10, while apigenin upregulated nuclear factor erythroid 2-related factor 2 (NRF2), NQO1, and HO-1 in ileum and jejunum on day 10. Both resveratrol and apigenin increased the mRNA expression of CLAUDIN-1 in ileum and jejunum on day 1 and that of ZO-1 (zonula occludens-1) in ileum on day 10 post-diquat-injection. These findings indicate that dietary supplementation with resveratrol and apigenin attenuates oxidative stress involving NRF2 signaling pathways in diquat-challenged pullets to some extent. These observations are valuable for the chicken industry and resveratrol and apigenin applications in animal husbandry.